SISTEM PEMBERIAN UPAH DI KEDAI Mr. CANGKIR SUMENEP - Endang Widyastuti; Rusnani Rusnani; Miftahol Arifin (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2023)
Mr. shop Cups is a business engaged in the typical culinary field of Sumenep. The impact of the Covid-19 pandemic has made the food industry suffer big losses, because there are rules to reduce interaction with other people or have to keep their distance. The impact of this policy was also felt by the Mr. Shop. Cup. This study aims to find out how the reward system at Mr. Sumenep cup. This type of research is qualitative. The sample data source in this study is the owner of the shop, Mr. Cup as a key informant. Data collection techniques in this study are observation, interviews and documentation. Data analysis techniques in this study are data reduction, data presentation and verification. The results of this study indicate that the wage system at the Mr.Cangkir Sumenep shop is based on a time system wage, namely daily.